2015
DOI: 10.4236/ojtr.2015.33010
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Barefoot vs. Shod Gait on Spinal Dynamics Using DIERS Formetric 4D and DIERS Pedoscan Systems

Abstract: Barefoot running is increasing in popularity within the running community, yet the biomechanical differences compared to traditional shod running are not well understood. This study investigates the changes in spinal dynamics during the gait cycle of runners wearing traditional running shoes (shod) compared to those wearing no shoes (barefoot). Pedal force distribution, kyphotic angle, lordotic angle, and trunk inclination were measured during shod and barefoot gait at three different speeds on a treadmill. Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 3 publications
1
8
0
Order By: Relevance
“…Basic descriptive statistics analysis was performed. To assess the normality of the distribution of variables, we used the Kolmogorov‒Smirnov test [ 40 ]. To establish the relationship between the studied variables, we used the Spearman rank correlation test [ 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…Basic descriptive statistics analysis was performed. To assess the normality of the distribution of variables, we used the Kolmogorov‒Smirnov test [ 40 ]. To establish the relationship between the studied variables, we used the Spearman rank correlation test [ 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…Analyses of static load (WB) distribution, postural sway based on CoP movement, surface topography of body posture, and gait were carried out using DIERS Formetric 4D system (DIERS International GmbH, Germany), a light-optical scanning method based on video raster stereography (13)(14)(15)(16). The system projects a line grid on the back of the patient, recorded by an imaging unit.…”
Section: Examinationmentioning
confidence: 99%
“…The system projects a line grid on the back of the patient, recorded by an imaging unit. A computer software analyzes the line curvature and generates a three-dimensional model of the body surface using photogrammetry (13)(14)(15)(16).…”
Section: Examinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Girdler et al [5] illustrated that the DIERS formetric scanner can contribute to AIS diagnosis and monitor without radiation exposure. Through measuring spine posture difference, it was found that DIERS 4D Formetric system can evaluate the differences of trunk inclination and kyphotic angle between barefoot and shod runners [19]. Spine morphology is also a crucial index for acute and chronic low back pain evaluation [1].…”
Section: Introductionmentioning
confidence: 99%